A Study on Investor Perception of Investing in IPO and Direct Listing Among the People Living in Ahmedabad City - Davda, Yashvi; Vidani, Jignesh; Patel , Jay (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study provides an in-depth examination of the consulting services offered by Head Quest HR Solutions LLP; a reputed HR consulting company based in Ahmedabad. The goals of the study are to examine the variety of services provided, the technologies used, and the efficiency of these services in improving organizational performance. This study combines quantitative information from structured customer surveys with qualitative data from semi-structured interviews with key stakeholders, through the use of a mixed-methods methodology. According to research, Head Quest HR Solutions LLP uses several approaches that are customized to match the specific needs of its clients. These approaches enhance employee engagement, talent management, and organizational development overall. Even when facing hurdles such as quantifying long-term impact and matching recommendations with customer culture, the company has proven quite successful in providing value-added services. This study provides suggestions to improve the efficiency and effectiveness of consulting services besides providing practical information on best practices in HR consulting.